Transforming growth factor-β/Smad - signalling pathway and conjunctival remodelling in vernal keratoconjunctivitis - Leonardi, A.; Di Stefano, A.; Motterle, L.; Zavan, B.; Abatangelo, G.; Brun, P. (Clinical and experimental allergy, 2011)
Summary Background Vernal keratoconjunctivitis (VKC) is a chronic ocular allergic inflammation characterized by corneal complications and the formation of giant papillae. Sma‐ and Mad‐related proteins (Smad) modulate extracellular matrix gene expression during wound healing, inflammation and tissue remodelling. Objective To investigate the relationship between allergic inflammation and TGF‐β/Smad signalling pathway, expression in VKC patients and in primary cultured conjunctival fibroblasts exposed to mediators found previously over‐expressed in VKC. Methods Smad‐2, ‐3, ‐7, phospho‐(p)Smads, TGF‐β1 and ‐β2 were evaluated in the conjunctiva of normal subjects (CT) and VKC patients by immunohistochemistry. The expression of Smads, pro‐collagen I (PIP), TGF‐β1, ‐β2, mitogen‐activated protein kinase (p38/MAPK), c‐Jun N‐terminal kinase (JNK) and extracellular signal‐regulated kinase (ERK1/2) were also determined in conjunctival fibroblast cultures exposed to histamine, IL‐4, ‐13, TGF‐β1, IFN‐γ and TNF‐α using immunostaining or RT‐PCR. Results Immunostaining for Smad‐2, ‐3, pSmad‐2, ‐3, TGF‐β1, ‐β2 and PIP was significantly increased in VKC stroma compared with CT. In conjunctival fibroblast cultures, Smad‐3 and PIP were stimulated by histamine, IL‐4, ‐13 and TGF‐β1 exposure, while PIP was reduced by IFN‐γ, and TNF‐α mRNA expression of Smad‐3 was increased by histamine, while Smad‐7 was reduced by IL‐4. In addition, histamine, IL‐4 and TNF‐α increased JNK and ERK1/2 expression. Conclusion and Clinical Relevance The TGF‐β/Smad signalling pathway is over‐expressed in VKC tissues and modulated in conjunctival fibroblasts by histamine, IL‐4, TGF‐β1 and TNF‐α. These mechanisms may be involved in fibrillar collagen production, giant papillae formation and tissue remodelling typical of VKC and might provide new therapeutic targets for its treatment. Cite this as: A. Leonardi, A. Di Stefano, L. Motterle, B. Zavan, G. Abatangelo and P. Brun, Clinical & Experimental Allergy, 2011 (41) 52–60.